Is sedentary behaviour unhealthy and if so, does reducing it improve this?. Issue 2 (February 2017) - Chin, Shao‐Hua; Kahathuduwa, Chanaka; Binks, Martin
Summary: Purpose: To provide a qualitative synthesis of the available literature on the role of sedentary behavior in health. Aims: We sought to determine if (i) being sedentary 'causes' health problems and (ii) interventions to reduce sedentary behavior improve health status. Methods: PubMed and Google Scholar databases were utilized. Manuscripts published from 2001 to 2015 using specific keyword combinations (eg sedentary behavior, physical activity, sitting, intervention) were included and qualitatively reviewed. Results: Data is suggestive of an association of sedentary behavior and negative health indicators. The association between sedentary behavior and mortality is stronger. There is some limited evidence suggesting short‐term health benefit to reducing sedentary behavior. Discussion: Evidence linking sedentary behavior to negative health outcomes is incomplete and often largely associational in nature thus not allowing for causal inference. In addition, interventional literature frequently fails to measure health outcomes, relying instead on the erroneous endpoint of changing sedentary behavior alone. Conclusion: Taken as a whole the literature is suggestive that there may be value in reducing sedentary behavior to have modest impact on health. However, the magnitude of the benefit appears minor and must be considered before making largescale and potentially costly clinical and public health recommendations.